2017
DOI: 10.1111/psyp.12870
|View full text |Cite
|
Sign up to set email alerts
|

Misfortune may be a blessing in disguise: Fairness perception and emotion modulate decision making

Abstract: Fairness perception and equality during social interactions frequently elicit affective arousal and affect decision making. By integrating the dictator game and a probabilistic gambling task, this study aimed to investigate the effects of a negative experience induced by perceived unfairness on decision making using behavioral, model fitting, and electrophysiological approaches. Participants were randomly assigned to the neutral, harsh, or kind groups, which consisted of various asset allocation scenarios to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 78 publications
(129 reference statements)
0
5
0
1
Order By: Relevance
“…Previous studies have found that RewP amplitudes were modulated by short-term emotional experiences (Hajcak et al, 2003 ; Bress et al, 2015 ; Kaltwasser et al, 2016 ). For example, Liu et al ( 2017 ) found that negative emotional arousal increased the sensitivity to RPEs, and then elicited larger RewP amplitudes. In their study, participants joined a dictator game (a modified ultimatum game) first and then joined a gambling task.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have found that RewP amplitudes were modulated by short-term emotional experiences (Hajcak et al, 2003 ; Bress et al, 2015 ; Kaltwasser et al, 2016 ). For example, Liu et al ( 2017 ) found that negative emotional arousal increased the sensitivity to RPEs, and then elicited larger RewP amplitudes. In their study, participants joined a dictator game (a modified ultimatum game) first and then joined a gambling task.…”
Section: Discussionmentioning
confidence: 99%
“…They found that larger RewP amplitudes were elicited in the gambling task when participants experienced harsh treatment (gained less than the opponents) in the dictator game than when they experienced favorable treatment (gained more than the opponents) or equal treatment (gained equal to the opponents). Liu et al ( 2017 ) proposed that participants who received harsh treatment were in disadvantageous circumstances. The disadvantageous circumstances would arouse the participants’ negative emotions and then intensify the RPE signals to elicit larger RewP amplitudes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…们 究 竟 是 怎 样 在 公 平 和 利 益 之 间 进 行 权 衡 的 (Andersen, Gneezy, Kajackaite, & Marx, 2018;Aoki, Yomogida, & Matsumoto, 2015)。最经典的研究是采 用涉及自我和他人利害关系的博弈论范式(特别是 独 裁 者 博 弈 和 最 后 通 牒 博 弈 )开 展 的 研 究 (Güth, Schmittberger, & Schwarze, 1982;Kahneman, Knetsch, & Thaler, 1986;Thaler, 1988)。一般的结论是, 人们 并非像传统经济学设想的那样唯利是图, 公平偏好 在 经 济 决 策 任 务 上 扮 演 着 同 样 重 要 的 角 色 (L iu, A c t a P s y c h o l o g i c a S i n i c a Hwang, Hsieh, Hsu, & Lai, 2017;Weiland, Hewig, Hecht, Mussel, & Miltner, 2012)。 这常常被作为人们 并非纯粹理性经济人论断的证据 (Güth et al, 1982;Weiland et al, 2012) (Bechtel, Liesch, & Scheve, 2018;Fehr & Schimdt, 1999;Gao et al, 2018;Yu, Calder, & Mobbs, 2014 Dawes, Fowler, Johnson, McElreath, & Smirnov, 2007;DeScioli et al, 2014) Abstract Distributive fairness is a basic behavioral norm and an important pursuit in our daily life, and it plays an important role in our social interactions. In studies of distributive fairness, individuals' fairness perception and the factors affecting it have gathered much research attention.…”
unclassified